French Language Online Cognitive Behavioral Therapy for Insomnia Disorder: A Randomized Controlled Trial - Lopez, Régis; Evangelista, Elisa; Barateau, Lucie; Chenini, Sofiene; Bosco, Adriana; Billiard, Michel; Bonte, Anne-Dominique; Béziat, Séverine; Jaussent, Isabelle; Dauvilliers, Yves (Frontiers in Neurology, 2019)
Background: Despite cognitive-behavioral therapy for insomnia (CBT-I) being the recommended treatment for insomnia disorder, its access remains very limited. Automated Internet-delivered CBT-I (eCBT-I) is an emerging cost-effective strategy for adults with insomnia, however no such program is currently available in French Language. We evaluated a French-speaking, eCBT-I intervention to improve insomnia disorder in comparison to minimal psychoeducation therapy (mPT). Methods: Forty-six adults with insomnia disorder were randomly allocated to eCBT-I or mPT. The eCBT-I program consisted of seven sessions that delivered the typical components of CBT-I during 12 weeks. The mPT provided structured and non-tailored information about sleep and insomnia during a one-hour session. Insomnia severity Index (ISI, primary outcome), measures of fatigue, sleepiness, anxiety, depressive symptoms and quality of life were collected at baseline and endpoint. Electronic Sleep diaries were completed over two-week periods pre- and post-intervention. Results: Compared to mPT, eCBT-I resulted in greater decrease in ISI scores between baseline and endpoint. Sleep diaries parameters improved in both groups, with a greater improvement in the eCBT-I group. Patients allocated to eCBT-I group also improved depressive, fatigue, anxiety symptoms and quality of life. Among patients with CNS-active drug at baseline, 91.7% reduced or stopped their hypnotic medication, and 16.7% in the mPT group. Conclusions: The present eCBT-I program seems feasible, acceptable and effective in reducing insomnia severity and insomnia-related functional outcomes in this small clinically-derived population. Given the high prevalence of insomnia, our data are supportive of the use of such program as an effective alternative to treat insomnia in daily clinical practice in French speaking countries.